Peningkatan Kompetensi Guru Dalam Pemanfaatan Platform Digital Mendukung Pembelajaran Inovatif Di SMAN 8 Banda Aceh - Fatmawati, Fatmawati; Junaedy , Junaedy; Sari, Dian Vita; Mursyidah, Nelly (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2026)
Background:The digital transformation in education requires teachers to possess adequate competencies in utilizing technology to support innovative, interactive, and student-centered learning. However, the integration of digital platforms into classroom practices remains limited due to teachers’ varying levels of digital competence and experience. This community service program aimed to improve teachers’ competencies in utilizing digital platforms to support innovative learning implementation at SMAN 8 Banda Aceh. Methods:The program employed a participatory approach consisting of needs assessment, workshops, hands-on practice, mentoring, evaluation, and reflection activities. A total of 40 teachers from various subject areas participated in the program. The training materials included the use of Canva for developing digital learning media, Quizizz for gamified assessments, Google Workspace for collaborative learning, and Artificial Intelligence (AI) technologies to assist in instructional material development and creative learning activities. Program evaluation was conducted through participant observation, assessment of digital learning products, satisfaction questionnaires, and reflective discussions. Results: The results showed that participants successfully produced 18 interactive presentations using Canva, 10 digital modules, 8 Quizizz-based quizzes, and 4 evaluation instruments using Google Forms. Furthermore, teachers demonstrated improved competencies in designing digital learning media, developing technology-based assessments, integrating digital platforms into instructional practices, and utilizing AI as a learning support tool. The high level of participation and enthusiasm among participants indicated the effectiveness of the program in strengthening teachers’ digital literacy and technological competencies. Conclusion: In conclusion, the community service program successfully enhanced teachers’ competencies in utilizing digital platforms to support innovative learning in schools.